Seismic vulnerability of churches in Faial and Pico islands, Azores - Magalhães, J. M. (2013)
Earthquakes represent one of the main cause of serious damage and loss of historic and architectural heritage. Interventions to preserve these building should start with a careful knowledge and assessment of their seismic vulnerability, in order to support any needed retrofitting and strengthening measures. This paper proposes a procedure to register and diagnose of the level of damage on churches after the occurrence of an earthquake, and also to assess the seismic vulnerability of this type of construction. This procedure was applied to sixteen churches in the Azores islands which were hit by the July 9th 1998 earthquake. Belfries of church towers are elements with a particular seismic vulnerability. For this reason, and based on the Italian methodology proposed by the Linee Guida (2006), it is applied to belfries of two churches from Pico (Azores), a simplified mechanical model for assessment of seismic vulnerability of this type of structures.